HUBUNGAN PERSEPSI MAHASISWA TENTANG KELUARGA HARMONIS DENGAN KESIAPAN MENIKAH - Faris Abdurrahman; Mudjiran Mudjiran; Zadrian Ardi (Jurnal Neo Konseling, 2020)
The research method used in this research is a quantitative method with a descriptive correlational approach. The population in this study were students of the Faculty of Education, State University of Padang in 2016. This population was chosen because students in 2016 were final students who were approaching the age of marriage. The average age of students in 2016 was 22-23 years, with a population of 1336 students. The number of samples of 93 students obtained through proportional random sampling by administering the Linkert model scale. Data were analyzed using descriptive analysis techniques and correlational analysis. Testing the research hypothesis using the Pearson Product Moment correlation formula. The results showed: (1) on average, students 'perceptions of harmonious families were in the good category, (2) on average, students' readiness to marry was in the sufficiently ready category, (3) there was no significant relationship between student perceptions and readiness. married, while the correlation coefficient has a weak level of relationship, with a correlation coefficient of 0.022 (0.20 <KK ≤ 0.40) at a significance level of 0.836 (Sig. rhitung> 0.05) 0.836> 0.05 (no relationship significant).